Inhibition of ATP citrate lyase induces triglyceride accumulation with altered fatty acid composition in cancer cells. Issue 1 (18th December 2013) - Migita, Toshiro; Okabe, Sachiko; Ikeda, Kazutaka; Igarashi, Saori; Sugawara, Shoko; Tomida, Akihiro; Soga, Tomoyoshi; Taguchi, Ryo; Seimiya, Hiroyuki
Abstract : De novo lipogenesis is activated in most cancers and several lipogenic enzymes have been implicated as therapeutic targets. Here, we demonstrate a novel function of the lipogenic enzyme, ATP citrate lyase (ACLY), in lipid metabolism in cancer cells. ACLY depletion by small interfering RNAs caused growth suppression and/or apoptosis in a subset of cancer cell lines. To investigate the effect of ACLY inhibition on lipid metabolism, metabolome and transcriptome analysis was performed. ACLY depletion blocks the fatty acid chain elongation from C16 to C18 in triglyceride (TG), but not in other lipid classes. Meanwhile, wild‐type ACLY overexpression enhanced fatty acid elongation of TG, whereas an inactive mutant ACLY did not change it. ACLY depletion‐mediated blockade of fatty acid elongation was coincident with downregulation of long‐chain fatty acid elongase ELOVL6, which resides in endoplasmic reticulum (ER). Paradoxically, ACLY depletion‐mediated growth suppression was associated with TG accumulation. ACLY depletion downregulated the expression of carnitine palmitoyltransferase 1A, which is a mitochondrial fatty acid transporter. Consistent with this finding, metabolome analysis revealed that ACLY positively regulates the carnitine system, which plays as an essential cofactor for fatty acid transport across mitochondrial membrane. AICAR, an activator of mitochondrial fatty acid oxidation (FAO), significantly reduced ACLY depletion‐mediated TG accumulation. These data indicate that inhibition of ACLY might affect both fatty acid elongation in ER and FAO in mitochondria, thereby explaining the TG accumulation with altered fatty acid composition. This phenotype may be a hallmark of growth suppression mediated by ACLY inhibition. Abstract : What's new? Most cancers cells turn on lipid production, and lipogenic enzymes that get activated in tumor cells could make attractive targets for therapy. In this paper, the authors discovered that blocking the lipogenic enzyme ACLY in cancer cells can slow growth and even kill the cells. Getting rid of ACLY, they found, halts the elongation of triglyceride chains, and reduces the production of a molecule that carries fatty acids into the mitochondria. This insight into cancer metabolism could lead to new ways to stop tumors.